Harnessing the Potential of Several Local Indonesian Tuber-derived Starches as Pharmaceutical Excipients - Horison, Ronald; Surini, Silvia (UI Scholars Hub, 2024)
Starch is one of the widely required excipients in pharmaceutical dosage forms manufacturing. Indonesia’s rich biodiversity, encompassing tubers like arrowroot, taro beneng, porang, ganyong and yams, harbours the potential for novel starch excipient sources. These tubers provide starch variations with distinct functional properties influenced by the natural starch granules’ properties and amylose-amylopectin ratio. Previous research utilizing natural and modified starches from these tubers has demonstrated their potential in pharmaceutical formulation. These starch tubers have been studied and provided promising results in tablet formulation and film development. Additionally, they could be involved in developing more advanced dosage forms, such as starch nanoparticles and nanocrystals. The rich versatility of these tuber starches solidified a promising future for their development, offering significant advantages for both pharmaceutical technology and economic value perspectives. Optimization of the starch yield, mainly through extraction, is crucial to fully realizing the economic prospect of tuber-derived starches.